Membangun Hubungan Komisi Yudisial Dengan Mahkamah Agung Yang Ideal - Juanda; Ogiandhafiz Juanda (Jurnal Hukum Sasana, 2021)
The phenomenon of the relationship between the Judicial Commission (KY) and the Supreme Court (MA) has had its ups and downs, and there are still many misinterpretations, as well as no common paradigm. As a result, if left unchecked, it could have a wide-ranging impact on law enforcement and justice in Indonesia's justice system. There are many aspects that need to be developed namely by establishing common paradigm and evaluating each party’s duties and authorities in order to achieve a harmonious relationship and strong synergy. Based on the problematic relationship between the two state institutions, the author is interested in studying and discussing "Building an Ideal Relationship between the Judicial Commission and the Supreme Court”. In order to examine and discuss the issue more fundamentally, the writer formulates the problem as follows: "How is the effort to build an ideal relationship between the judicial commission and the Supreme Court?” The method used is in accordance with the type of research, which is normative juridical and involves the use of both primary and secondary legal materials. While the analysis that was used is a qualitative juridical analysis. The conclusion is that the paradigm of the relationship that must be built between the judicial commission and the Supreme Court is the paradigm of equality, systematic, professionalism and proportionality. Efforts that can be made are to strengthen communication, coordination, and review and evaluate various obstacles and weaknesses regarding the position, function, and authority between the two state institutions by involving experts or neutral national figures. Revising from the aspect of the legislation is included.